The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/(sici)1097-0215(19970220)74:1<35::aid-ijc7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, sequencing and expression of the mRNA encoding human Cdx1 and Cdx2 homeobox. Down-regulation of Cdx1 and Cdx2 mRNA expression during colorectal carcinogenesis

Abstract: Defining the molecular mechanisms involved in cancer formation and progression is still a major challenge in colorectal-cancer research. Our strategy was to characterize genes whose expression is altered during colorectal carcinogenesis. To this end, the phenotype of a colorectal tumour was previously established by partial sequencing of a large number of its transcripts and the genes of interest were selected by differential screening on high-density filters with mRNA of colorectal cancer and normal adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
132
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 28 publications
16
132
1
1
Order By: Relevance
“…The ras-dependent decrease in Cdx-2 expression reported here in vitro in human colonic Caco-2 and HT-29 cells is fully consistent with the decline of expression of this tumour-suppressor gene that correlates to the pathological grade in human colorectal cancers and in chemically-induced colonic tumours in the rat (Ee et al, 1995;Mallo et al, 1997). Our results therefore suggest that in vivo, like in cultured cells, Cdx-2 is a target of oncogenic ras.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The ras-dependent decrease in Cdx-2 expression reported here in vitro in human colonic Caco-2 and HT-29 cells is fully consistent with the decline of expression of this tumour-suppressor gene that correlates to the pathological grade in human colorectal cancers and in chemically-induced colonic tumours in the rat (Ee et al, 1995;Mallo et al, 1997). Our results therefore suggest that in vivo, like in cultured cells, Cdx-2 is a target of oncogenic ras.…”
Section: Discussionsupporting
confidence: 84%
“…The stimulation of Cdx-1 reported in this study by oncogenic ras in colonic Caco-2 cells is consistent with the onset of expression found in metaplasic areas of oesophagus and gastric cancers, since oncogenic ras activation is often associated with well di erentiated tumours of the upper digestive tract (Peddanna et al, 1995). Thus, during early events in the progression of normal colonic epithelium to adenoma, oncogenic ras activation would stimulate Cdx-1; additional genetic alterations may subsequently downregulate this gene during further progression to adenocarcinoma and distant metastasis, as observed by Silberg et al (1997), Mallo et al (1997) and Vider et al (1997). This hypothesis is supported by the fact that the decrease of Cdx-1 in colonic cancers was found not to be related to the pathological grade (Silberg et al, 1997), in contrast to what was reported for Cdx-2 (Ee et al, 1995).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…4 Similarly, CDX2 has been detected in human fetal intestine at both the mRNA and protein level. [5][6][7] Conditional expression of CDX2 in an undifferentiated intestinal cell line results in the formation of multicellular structures with demonstrable enterocyte and goblet cell features, supporting a role for CDX2 in intestinal differentiation. 8 This likely reflects direct upregulation of transcription from genes such as liver-intestine cadherin and MUC2 by CDX2, as has been shown in other cell lines.…”
mentioning
confidence: 91%